2005
DOI: 10.1191/0269215505cr905oa
|View full text |Cite
|
Sign up to set email alerts
|

Construct validity and reliability of the Rivermead Post-Concussion Symptoms Questionnaire

Abstract: As currently used, the RPQ does not meet modern psychometric standards. Its 16 items do not tap into the same underlying construct and should not be summated in a single score. When the RPQ is split into two separate scales, the RPQ-13 and the RPQ-3, each set of items forms a unidimensional construct for people with head injury at three months post injury. These scales show good test-retest reliability and adequate external construct validity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
217
1
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(237 citation statements)
references
References 22 publications
12
217
1
3
Order By: Relevance
“…The RPSQ is a 16-item concussion symptom inventory checklist that has been used extensively in both adult and pediatric studies of mTBI, 7,13,14 has shown a high degree of inter-rater and test-retest reliability, 15,16 and is valid and unbiased in young children. 14,17 The questionnaire was available to study participants in both English and Spanish.…”
Section: Discussionmentioning
confidence: 99%
“…The RPSQ is a 16-item concussion symptom inventory checklist that has been used extensively in both adult and pediatric studies of mTBI, 7,13,14 has shown a high degree of inter-rater and test-retest reliability, 15,16 and is valid and unbiased in young children. 14,17 The questionnaire was available to study participants in both English and Spanish.…”
Section: Discussionmentioning
confidence: 99%
“…It consists of 16 items assessing severity of symptoms in the last 24 hours in comparison to premorbid levels. It is a valid and reliable measure in TBI (55). The total score ranges from 0 to 64.…”
Section: Post-concussion Symptomsmentioning
confidence: 99%
“…The RPQ is commonly used to assess the severity of symptoms after mild or moderate TBI (55). It consists of 16 items assessing severity of symptoms in the last 24 hours in comparison to premorbid levels.…”
Section: Post-concussion Symptomsmentioning
confidence: 99%
“…The Rivermead Post Concussion Symptoms Questionnaire 34,35 and the Brief Symptom Inventory, 36 from which the Global Severity Index (GSI) was calculated, were also collected as self-report symptom measures. Socioeconomic Composite Index (SCI) scores were calculated based on annual family income, level of education (maternal education for participants younger than 18 years old), and occupational prestige.…”
Section: Methodsmentioning
confidence: 99%